Effect of different placement techniques on color stability and surface roughness of resin composites - Fernanda KERPEL; Ana Carolina BAMBERG; Gabriel Ferreira NICOLOSO; Leonardo Lamberti MIOTTI; Andressa DALMOLIN; Luciana Abitante SWAROWSKY; Marcela MARQUEZAN; Letícia Brandão DURAND (Universidade Estadual Paulista, 2021)
Abstract Introduction Longevity and clinical success of dental restorations can be influenced by many factors during the restorative procedures. Objective This study aimed to evaluate the influence of different placement techniques on color stability and surface roughness of two resin composites. Material and method The groups of specimens (n=10) were divided according to resin composite (FiltekTM Z250 XT and FiltekTM Z350 XT) and placement technique: Mylar strip, spatula, dry brush, modeling liquid, and surface sealant. Color stability and surface roughness were accessed using a spectrophotometer (CIELab color space) and a rugosimeter (standard cutoff of 0.8 mm), respectively, after water storage. Subsequently, the specimens were immersed in coffee for 48 h and final color was measured. The data were analyzed using ANOVA and the Tukey's post hoc test (α=5%) and the correlation between surface roughness (Ra) and color change (∆Eab) was assessed using the Pearson's correlation coefficient. Result The different placement techniques influenced Ra and ∆Eab on both resin composites. The groups treated with surface sealant showed greater difference in ∆Eab for both resin composites. The FiltekTM Z250 XT resin showed greater color stability compared with the FiltekTM Z350 XT resin regardless of the placement technique used. Ra of each placement technique was similar among the resin composites except for the FiltekTM Z350 XT modeling liquid group, which presented lower Ra values compared with those of FiltekTM Z250 XT. A correlation between Ra and staining was identified (p=0.268). Conclusion Color stability and Ra are influenced by different placement techniques.